WEED MANAGEMENT UNDER NO-TILL TO INCREASE THE BENEFITS OF THE TRIPARTITE SYMBIOSIS - Alho, Luis (2012)
In southern regions of Europe subclover (Trifolium subterraneum L.), inoculated with rhizobia, is commonly sown in acid soils that are marginal for arable crop production. The rate of success of these pastures is small both in terms of plant growth and nodulation with the introduced rhizobia. Manganese toxicity is frequently considered to be a contributory factor. Nevertheless, other native legumes, particularly Ornithopus, are commonly found to grow satisfactorily under these conditions. Knowing that Ornithopus is a highly mycotrophic plant, we hypothesized that preserving the extraradical mycelium (ERM) of mycorrhizal fungi associated with its roots at the time for seeding subclover would allow for a better performance of subclover through an enhanced tripartite symbiosis (legume-rhizobia-mycorrhizal fungi). To test this hypothesis a pot experiment was conducted in a soil where manganese toxicity was known to occur. Ornithopus compressus and Silene gallica (a non-mycotrophic plant) and two different weed control methods were used to promote different levels of clover AM colonization. The weeds were allowed to growth for 6 weeks and controlled by glyphosate or mechanically with soil disturbance, prior to the seeding of inoculated subclover (T. subterraneum cv. Nungarin). The only treatment where the ERM was kept intact was Ornithopus controlled by glyphosate. Three weeks after planting, arbuscular mycorrhiza (AM) colonization of the clover under this treatment was significantly greater (3 times) than all the other treatments. In consequence, there was significant improvement in shoot dry weight (5 times), nodule dry weight (7 times) and N accumulation (4 times) of clover. The results were consistent with the hypothesis that the roots of the clover seedlings connected to the intact ERM developed by Ornithopus promoting the tripartite symbiosis .